Does Painful Heels in Ankylosing Spondylitis Demonstrate Distinctive Features on Plain Radiographs: A Study of 104 Cases - Kim, Tae-Hwan; Lee, Seunghun; Sung, Il-Hoon; Kim, Sung-Jae; Sung, Hyo-Kyung; Hur, Jae-Seung (Journal of rheumatic diseases, 2017)
Objective. To investigate simple radiographic findings on painful heels in ankylosing spondylitis (AS). Heel radiography in most studies was from AS patients’ non-painful heel. Methods. Seventy AS patients (34 bilateral cases) with heel pain at the time digital radiographs were taken were studied. Standing lateral views (104 radiographs) of the heel were reviewed. Associations between radiologic abnormalities and disease duration and among various abnormal findings were analyzed. Results. Ninety-six (93.4%) had radiographic abnormalities (82.7% in soft tissues/61.5% in bone). Abnormalities of bone only were observed in 9.6%, of the soft tissues only in 30.8%, and of both were 51.9%. These included Kager’s triangle’s blurring (77.9%), posterior soft tissue swellings near the Achilles tendon insertion (65.4%), obliterations of the retrocalcaneal recess (65.4%), erosions of the superior pole of the posterior calcaneus (31.7%), subplantar irregular spurs (20.2%), posterior traction spurs (16.3%), subplantar erosions (14.4%) and cortical thickenings of the inferior calcaneal body (5.8%). There was a significant association between swelling in the posterior soft tissue and obliteration of the retrocalcaneal recess (p＜0.001). Conclusion. Digital radiography in AS is useful for observing not only bony lesions but also soft tissue abnormalities of the heel, particularly of the posterior heel. For assessing the symptomatic enthesitis of the Achilles, this simple and quick diagnostic tool is valuable when examining for soft tissues’ alterations of the posterior heel. (J Rheum Dis 2017;24:93-98) KCI Citation Count: 0